Clay and Clay Minerals - Morari Do Nascimento, Gustavo (IntechOpen, 2021)
New two-dimensional materials based on clays and clay minerals are attracting attention for their outstanding properties that make them useful as hosts or supporting matrixes in applications such as pharmaceuticals, tissue engineering, environmental remediation, biosensors, filtration, wound dressings, drug delivery, and more. This book is a comprehensive overview of clay science and technology, focusing on synthesis, characterization, simulation, and applications. Chapters cover such topics as polymer-clay nanocomposites, the structure and properties of different clays, the use of clays for environmental remediation, and much more.